Opposite effects of transforming growth factor-β1 and vascular endothelial growth factor on the degeneration of aortic valvular interstitial cell are modified by the extracellular matrix protein fibronectin: implications for heart valve engineering - Mambou Kamdem Gwanmesia, Patricia Neh; Ziegler, Heiko; Eurich, Rosa; Barth, Mareike; Kamiya, Hiroyuki; Karck, Matthias; Lichtenberg, Artur; Akhyari, Payam (Tissue engineering, 2010)
The enhancement of valvular interstitial cell (VIC) calcification by transforming growth factor-β1 (TGF-β1) and the endothelial inducing effect of vascular endothelial growth factor (VEGF) have been demonstrated. Here we report the modulating properties of extracellular matrix (ECM) modification on VIC calcification in the presence of TGF-β1 and VEGF. Ovine aortic VICs cultured on collagen, fibronectin, laminin, or uncoated surfaces were exposed to TGF-β1, VEGF, or left untreated. VEGF significantly inhibited the formation of calcific nodules independent of ECM Protein coating (p < 0.05). TGF-β1 exposition resulted in the formation of calcific nodules on collagen, laminin, and uncoated control surfaces. In contrast, fibronectin coating resulted in significantly reduced nodule formation despite TGF-β1 administration. Further, we showed a marked increase of apoptotic and dead cells in calcific nodules. Overall, our data demonstrate that, an additive protective effect on VICs can be achieved by providing specific growth factors or a specific ECM environment. Here, VEGF administration inhibited calcification and apoptosis, particularly in combination with fibronectin coating. This combination appears to be a promising tool for modification of heart valve scaffolds for tissue engineering purposes and preclinical trials.
Gesehen am 06.06.2023